THE PROBLEM OF TEACHERS DEVELOPING SHEET WORK OF STUDENTS (LKPD) HIGH SCHOOL BIOLOGY BASED SCIENTIFIC APPROACH - Leni Triyani; Makrina Tindangen; Akhmad Akhmad (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The problem that often occurs is a lack of understanding of teachers to develop LKPD learning tools to create creative and innovative learning so that solutions are needed to solve the problems that occur, the purpose of this study is to find out what problems are faced by teachers when developing LKPD in SMA Negeri at Muara Badak which is based on a scientific approach in improving students' critical thinking skills . The research method used is a percentage and is described in accordance with the findings. Result Research shows that 80% of teachers do not understand how to develop LKPD learning tools for each component . The teacher's lack of understanding regarding how to develop LKPD learning tools that are adapted to learning materials to create creative and innovative learning. Based on the results of this study, it can be concluded that it is necessary to develop LKPD that is in accordance with the objectives of learning and is able to improve students' critical thinking skills.